PENGARUH KOMPENSASI DAN FASILITAS KERJA TERHADAP KINERJA KARYAWAN DI HOTEL PURI MEGA JAKARTA - Angger Asa Yoya; Priyanto (Human Capital Development, 2016)
Purpose- This study aimed to determine the effect of compensation and working facilities with the performance of employees at Puri Mega Hotel Jakarta Design/methology/approach- This study used two dependent variable that compensation and working facilities to the independent variable is the performance of employees. The population is employees Puri Mega Hotel Jakarta, with the samples used are used in this study as many as 100 people. Based on research hasi through validity test, reliability test, classic assumption test (norm. ality test, multicollinearity, heteroscedasticity test and linearity test). Findings- While testing the hypothesis include tests F, t test and analysis of partial correlation and coefficient of determinationFrom the analysis it can be seen that the compensation (X1) and work facilities (X2) have an influence on employee performance (Y) either partially or simultaneously. Research limitations- The limitation of this research lies on its scope of object, and the limited variables involved. It is then suggested for the next research that other variable such as motivation, and other exogen variable can be deployed too. This results may not be applicable in the same line of business. Practical implications- The manager of human resource shall maintain and develop the potential of employees by providing a combination of compensation, and working facilities n in human resources development. The Originality- This is done exclusively for the Puri Mega Hotel Jakarta